(untitled) (Research, Society and Development, 2020)
This study evaluated the adaptive capacity and variations in physiological parameters of four male goats originate from a temperate region (Alpine breed) in a tropical climate over twelve months. The ambient temperature, relative humidity, and temperature via a black globe thermometer were evaluated to calculate the black globe temperature and humidity index; they were collected five times during the day, three times during the week, and during the four annual seasons. Every fortnight throughout the experimental period, respiratory and heart rates as well as rectal and surface temperatures of the animals were measured in the morning, and blood samples were acquired for hormonal levels (cortisol, T3, and T4) and complete blood count. There was a difference between the mean values of surface temperature, respiratory rate, hormones, and some hematological parameters (total protein and monocytes) between the seasons (P<0.05). However, no differences were observed in cases of heat stress, based on the fact that physiological parameters were within normal and expected limits for goats. Thus, it is concluded that the male goats of the Alpine breed, when reared intensively, maintain homeothermia and are greatly adaptable to the conditions of the tropical climate.